Charisma is not enough: measuring short- and long-term environmental consciousness in wildlife tourism activities - Marcías, María Laura; Salvadeo, Christian; Salgado-Beltrán, Lizbeth; García-Castañeda, Omar (Frontiers in Conservation Science, 2025)
Nature-based tourism, such as whale watching and swimming with whale sharks, is rapidly growing worldwide. Although there is no clear classification, whale watching is often referred to as ecotourism or sustainable tourism. However, one of the key principles of true ecotourism is that it promotes, among other things, the generation of environmental education and awareness. The purpose of this research was to evaluate the effect of tourism activities with charismatic species in tourists’ environmental consciousness. The study was carried out in three stages via surveys to participants of two main activities (snorkeling with whale sharks and gray whale watching) in Baja California Sur, Mexico: 1) one before the activity where socio-demographic, circumstantial variables, and initial environmental awareness and pro-environmental behavior were measured; 2) one immediately after, evaluating aspects of the experience and awareness in the short term, and, 3) Four months later via e-mail to evaluate environmental consciousness in the long term. A total of 542 surveys were obtained in the first two stages, and 200 surveys in the third stage. A Structural Equation Model analysis was performed to test causal relationships between the activities and environmental consciousness. Our results show that the experience with a charismatic species had a significant and positive effect on short-term environmental awareness. However, there was no significant effect of the experience on their long-term environmental consciousness. Implications for the actors involved in nature-based tourism activities are discussed, highlighting the need to implement globally used strategies but applying them in the local context.